Early Ideas on Sovereign Bankruptcy Reorganization : A Survey - Rogoff, Kenneth; Zettelmeyer, Jeromin (Washington, D.C. : International Monetary Fund, 2002)
This paper surveys early intellectual antecedents of the Krueger (2001) proposal for creating bankruptcy reorganization procedures at the international level. We focus on actual proposals for new procedures made from the late 1970s up to an influential lecture by Sachs (1995), with brief reference to the formal economics literature on sovereign debt. Beginning with a paper by Oechsli (1981), several key contributions are made during this period, including the analogy with domestic bankruptcy procedures, an understanding of the inefficiencies in international lending that might justify such procedures, and specific institutional and legal suggestions that continue to play a role in the current debate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet